Analysis of water jet propeller hydrodynamic performance based on CFD. (July 2020) - Liu, Xianlong; Luo, Jinwang; Liu, Cheng
Abstract: The method of ducted propeller design is used to design the impeller of water jet propeller. The method of space transformation is used to transform the two-dimensional NACA airfoil into three-dimensional airfoil. The flow field model of water jet propeller is generated by structured grid. The SST model is using for calculation and the maximum thrust is 170.4N when the rotation speed is 4000R / min and the inlet velocity is 2m / s.